2017
DOI: 10.1002/2016jd026180
|View full text |Cite
|
Sign up to set email alerts
|

The combined risk of extreme tropical cyclone winds and storm surges along the U.S. Gulf of Mexico Coast

Abstract: Tropical cyclones, with their nearshore high wind speeds and deep storm surges, frequently strike the United States Gulf of Mexico coastline influencing millions of people and disrupting offshore economic activities. The combined risk of occurrence of tropical cyclone nearshore wind speeds and storm surges is assessed at 22 coastal cities throughout the United States Gulf of Mexico. The models used are extreme value copulas fitted with margins defined by the generalized Pareto distribution or combinations of W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
1
13
0
1
Order By: Relevance
“…The elliptical copula model with description can be found in Bushra (). This result aligns with those of Trepanier et al (; ), who suggested that Archimedean Gumbel‐based copulas are effective for representing dependence in arbitrarily high dimensions even when only one parameter governs the strength of dependence. Therefore, the Archimedean copula is used to calculate the return periods for wind and surge.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The elliptical copula model with description can be found in Bushra (). This result aligns with those of Trepanier et al (; ), who suggested that Archimedean Gumbel‐based copulas are effective for representing dependence in arbitrarily high dimensions even when only one parameter governs the strength of dependence. Therefore, the Archimedean copula is used to calculate the return periods for wind and surge.…”
Section: Resultssupporting
confidence: 91%
“…From these results, it seems that in the BoB, the risk of combined surge heights and wind speeds (even the lowest) are comparably higher than those in the Gulf of Mexico, where Trepanier et al () modelled storm surge and wind‐induced combined risk at Galveston, Texas; and later, at 22 Gulf Coast cities ranging from South Padre Island, Texas, to Key West, Florida (Trepanier et al , ). Rich data availability in the coastal Gulf of Mexico region allowed for a varying spatial picture of combined wind and surge risk in Trepanier et al (). The BoB has a wide‐ranging coastline and likely experiences varying risk similar to the Gulf of Mexico, but due to the sparseness of data, the same level of spatial resolution cannot be attained.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations